Kidney failure and the federal government - Rettig, Richard A.; Levinsky, Norman G. (Norman George), 1929- (National Academy Press, 1991)
Overview -- Summary -- Introduction -- Patients and providers -- Perspectives of ESRD patients -- Ethical issues -- The patient population -- The ESRD patient population: special groups -- Structure of the provider community -- Access -- Access problems of ESRD patients -- Access to kidney transplantation -- Reimbursement and quality -- Medicare ESRD payment policy -- Reimbursement effects on quality -- Outpatient dialysis reimbursement issues -- Quality assessment and assurance -- Data and research -- Data systems -- Research needs.